Ceftazidime-Induced Neurotoxicity in an 80-Year-Old Female With Renal Dysfunction: A Case Report. (June 2022) - Amirouche, Laetissia; Cerulli-Kanellopoulos, Alexandra; Landry, Sébastien; LeBlanc, Véronique C.; Léger, Ghislain
Neurological toxicity is a relatively rare adverse reaction reported in elderly patients treated with cephalosporins. We present a case of ceftazidime-induced encephalopathy in the context of acute kidney injury in an 80-year-old female treated for a Pseudomonas aeruginosa prosthetic joint infection. During the course of treatment, the patient developed sudden confusion and disorientation. The patient's mental state progressively worsened, eventually leading to intubation and admission to the intensive care unit. As imaging and laboratory analyses revealed no alternative causes explaining the patient's symptoms, ceftazidime was stopped under the suspicion of drug-induced neurotoxicity. Shortly after ceftazidime discontinuation, the patient's condition drastically improved and returned to baseline within 5 days. This case reveals the potential severity of cephalosporin-induced neurotoxicity in elderly patients and highlights the importance of quickly detecting such adverse events in order to prevent dire outcomes.